Phonetic Errors Produced by Students of Speaking 2 of the English Department of Petra Christian University - Oscar Jodi Putra (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This study analyzed phonetic errors found in the students of Speaking 2 of the English Department of Petra Christian University. There were sixteen students taking part in this study. The main theories for this study are from Celce-Murcia, Brinton, & Goodwin (2004) on the production of English consonants and Moeliono and Dardjowidjojo (2003) on the production of Indonesian consonants. The method used was qualitative approach. The researcher had the students read four short passages to find out the kinds of phonetic errors and interviewed them to find out what factors that might affect their pronunciation, which contains phonetic errors. The findings revealed fourteen deviation patterns found from the four target consonants observed, mainly caused by the non-existence of the target sounds in students’ mother tongue. Additionally, the findings also showed that the learners’ attitude towards the language was the most important factor influencing their pronunciation level. Keywords: Phonetic, errors, phonetic errors